GENERALIZED ERYTHEMATOUS-URTICARIAL DERMATITIS AND RESPIRATORY INFECTIONAS A MANIFESTATION OF COMBINED PARVOVIRUS B19 AND MYCOPLASMA PNEUMONIAE INFECTION IN A 2-YEAR-OLD CHILD - G. V. Petrova; S. S. Agapova; M. V. Mozzhukhina; E. P. Tymoshenko; N. S. Pavlov; E. P. Kudryavtzeva; N. P. Makina; M. V. Shcherbakova (LLC "Diagnostics and Vaccines", 2018)
The article describes the clinical case of combined skin lesions in the form of generalized erythematous-urticarial dermatitis and the respiratory tract in the form of rhinoadenopharyngitis, simple bronchitis, in a child of 2 years. Caused by parvovirus B19 and Мycoplasma pneumoniae. The problems of diagnosis, treatment, variety of clinical manifestations of parvovirus B19 infection and Мycoplasma pneumoniae are discussed.